2019
DOI: 10.3390/v11110974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immunogenetic Biomarkers in the Clinical Outcome of HTLV-1 Infected Persons

Abstract: Human T-lymphotropic virus 1, a member of the Retroviridae family, causes a neglected, silent, persistent infection affecting circa 5 to 10 million people around the world, with biology, immune pathology, clinical diseases, epidemiology, and laboratory issues still unsolved. Most of the infected subjects are asymptomatic, but severe clinical disorders appear as a neurodegenerative disease (HTLV-1 associated myelopathy—HAM) or a lymphoprolipherative disorder (Adult T Leukemia/Lymphoma—ATLL) and in other target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 94 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…Chronic HTLV-1 infection is associated with unrelenting immune activation accompanied by high levels of both pro- and anti-inflammatory cytokines [ 80 , 81 ]. This outcome likely results from the host’s continuous, albeit unsuccessful, attempts to eradicate viral infection and maintain tissue homeostasis [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HTLV-1 infection is associated with unrelenting immune activation accompanied by high levels of both pro- and anti-inflammatory cytokines [ 80 , 81 ]. This outcome likely results from the host’s continuous, albeit unsuccessful, attempts to eradicate viral infection and maintain tissue homeostasis [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the protective effects of HLA-A ∗ 02:07 and HLA-C ∗ 08 and the detrimental effects of HLA-B ∗ 54 has been demonstrated in southern Japan ( Boelen et al, 2018 ). HLA-Cw ∗ 08 was similarly seen in both ACs and HAM / TSP patients in a Brazilian study, but was associated with a protective effect in Japan and higher susceptibility to HAM/TSP in Iran ( Vallinoto et al, 2019 ). Class II HLA-DRB1 ∗ 0101 has been identified as a predisposing factor to the disease in Japan, Iran, and Spain and it has been shown that the effect is exacerbated in the absence of the protective effect of HLA-A ∗ 02 ( Jeffery et al, 1999 ; Saito, 2019 ; Vallinoto et al, 2019 ).…”
Section: Host Factors In Development Of Ham/tspmentioning
confidence: 98%
“…HLA-Cw ∗ 08 was similarly seen in both ACs and HAM / TSP patients in a Brazilian study, but was associated with a protective effect in Japan and higher susceptibility to HAM/TSP in Iran ( Vallinoto et al, 2019 ). Class II HLA-DRB1 ∗ 0101 has been identified as a predisposing factor to the disease in Japan, Iran, and Spain and it has been shown that the effect is exacerbated in the absence of the protective effect of HLA-A ∗ 02 ( Jeffery et al, 1999 ; Saito, 2019 ; Vallinoto et al, 2019 ). Haplotype HLA-B ∗ 0702-Cw ∗ 0702-DRB1 ∗ 0101-DQB1 ∗ 0501 is also predisposing in the absence of HLA-A ∗ 02 ( Catalan-Soares et al, 2009 ).…”
Section: Host Factors In Development Of Ham/tspmentioning
confidence: 98%
See 1 more Smart Citation
“…Viruses 2022, 14, 1175 2 of 11 have been the focus of several studies in the search for biomarkers that can explain the evolution of infection and the development of associated diseases. Genetic variations in genes encoding cytokines, restriction factors, and proteins that activate apoptosis have been associated with the development of HAM and other inflammatory manifestations associated with HTLV-1 [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%